Electrode for secondary batteries, secondary battery, manufacturing method of electrode for secondary batteries, and manufacturing method of secondary battery
By using active material particles of high longitudinal ratios and unevenly distributed microparticles in the active material layer of secondary battery electrode, the stress reduction problem caused by the reduced contact area between the active material layer and the current collector is solved, achieving higher adhesion strength and lower resistance.
Patent Information
- Application Number
- JP2023152513
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-04-02
AI Technical Summary
The existing secondary battery electrode reduces the contact area between the active material layer and the current collector, resulting in a reduced peel strength of the active material layer, which in turn causes a decrease in stress during battery manufacturing or during cycle testing.
Active material particles and microparticles with longitudinal ratios above 1.0 are used, and the microparticles are unevenly distributed in the active material layer, located between the active material particles, and unevenly distributed on the side of the current collector in the thickness direction of the active material layer to improve the contact area and adhesion strength of the active material layer and the current collector.
By increasing the contact area and adhesion strength of the active material layer with the current collector, the stress reduction problem of the active material layer peeling during battery manufacturing or during cycle tests is suppressed, while improving the conductivity and reducing the resistance.
Smart Images

Figure 2025044757000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electrode for a secondary battery, a secondary battery, a method for manufacturing an electrode for a secondary battery, and a method for manufacturing a secondary battery. [Background technology]
[0002] Secondary batteries are widely used in vehicles, information and communication technology (for example, personal computers, smartphones, etc.), power storage, and the like. In secondary battery electrodes, active materials (such as graphite) that have the property of being oriented in layers within the active material layer are used. For example, Patent Document 1 discloses a negative electrode containing an active material, which is graphite oriented by application of a magnetic field. For example, Patent Document 2 discloses a negative electrode including an active material layer having oriented graphite and a fine carbon material. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2003-197189 A [Patent Document 2] JP 2013-004307 A Summary of the Invention [Problem to be solved by the invention]
[0004] In order to obtain a secondary battery with high input and output, it is necessary to improve the diffusibility of conductive species (e.g., Li ions) in the electrode. For example, in Patent Documents 1 and 2, as one of the means, a magnetic field is applied to the electrode after coating, thereby orienting the active material in the active material layer so that the long axis direction of the active material is perpendicular to the current collector, thereby reducing the liquid resistance. However, in conventional secondary battery electrodes, the contact area between the current collector and the active material tends to decrease when the active material is oriented, which reduces the peel strength of the active material layer from the current collector and makes the active material layer more likely to peel off from the current collector due to the electrode winding process during battery production or the expansion and contraction of the active material during cycle testing, i.e., the stress may decrease. In view of the above circumstances, an object of the present disclosure is to provide an electrode for a secondary battery, a secondary battery, a method for manufacturing an electrode for a secondary battery, and a method for manufacturing a secondary battery, in which a reduction in stress due to peeling of an active material layer from a current collector is suppressed. [Means for solving the problem]
[0005] Means for solving the above problems include the following means. <1> A current collector; an active material layer provided on the current collector, the active material layer including microparticles and active material particles having an aspect ratio of more than 1.0; having the microparticles are interposed between a plurality of the active material particles and are unevenly distributed on the current collector side, The active material particles are oriented such that a longitudinal direction of the active material particles is substantially perpendicular to a surface direction of the current collector. <2> the microparticles are unevenly distributed in a region having a depth equivalent to 0.5 times the length (μm) of the long side of the active material particles in a thickness direction of the active material layer from the surface of the active material layer facing the current collector; <1> The secondary battery electrode according to claim 1, <3> the content of the microparticles in a region of the active material layer at a depth equivalent to 0.5 times the long side (μm) of the active material particles in a thickness direction of the active material layer from the surface of the active material layer facing the current collector is 8% by volume or more; <1> or <2> The secondary battery electrode according to claim 1, <4> a ratio (T / L) of a thickness T of a region of the active material layer on the current collector side where the microparticles are present to a long side L of the active material particles is 0.375 or more and 0.500 or less; <1> ~ <3> 13. The electrode for a secondary battery according to claim 12. <5> The active material particles are graphite. <1> ~ <4> 13. The electrode for a secondary battery according to claim 12. <6> For the negative electrode, <1> ~ <5> 13. The electrode for a secondary battery according to claim 12. <7> The microparticles have anisotropy. <1> ~ <6> 13. The electrode for a secondary battery according to claim 12. <8> The microparticles have an aspect ratio of 1.0 or more and 2.5 or less. <7> The secondary battery electrode according to claim 1, <9> the ratio (d / R) of the longitudinal length (d) of the microparticle to the longitudinal radius (R) of the active material particle is 0.625 or more and 1.000 or less; <1> ~ <8> 13. The electrode for a secondary battery according to claim 12. <10> the microparticles are interposed between a plurality of the active material particles and are unevenly distributed on both the current collector side and the side facing the current collector; <1> ~ <9> 13. The electrode for a secondary battery according to claim 12. <11> The microparticles have an average primary particle size of 4.58 μm or less. <1> ~ <10> 13. The electrode for a secondary battery according to claim 12. <12> <1> ~ <11> 2. A secondary battery comprising the electrode for a secondary battery according to claim 1. <13> A step of applying a first slurry containing active material particles and microparticles having an aspect ratio of more than 1.0 and a solvent onto a current collector; applying a second slurry containing the active material particles and a solvent but not containing the microparticles; orienting the active material particles in an active material layer such that their longitudinal directions are substantially perpendicular to a surface direction of the current collector; The method for producing an electrode for a secondary battery comprising the steps of: <14> <13> 2. A method for producing a secondary battery, comprising the step of producing a secondary battery comprising an electrode for a secondary battery produced by the method for producing an electrode for a secondary battery according to claim 1. Effect of the Invention
[0006] According to one embodiment of the present disclosure, there is provided a secondary battery electrode and a secondary battery in which a decrease in stress due to peeling of an active material layer from a current collector is suppressed. According to another embodiment of the present disclosure, there is provided a method for manufacturing an electrode for a secondary battery and a method for manufacturing a secondary battery in which a decrease in stress due to peeling of an active material layer from a current collector is suppressed. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a schematic cross-sectional view in the thickness direction of a conventional electrode for a secondary battery. [Diagram 2] FIG. 2 is a schematic cross-sectional view in the thickness direction of an electrode for a secondary battery in one embodiment of the present disclosure. [Diagram 3] FIG. 3 is a schematic cross-sectional view in the thickness direction of an electrode for a secondary battery in another embodiment of the present disclosure. [Figure 4] FIG. 4 is a schematic cross-sectional view in the thickness direction of the active material layer models in Example 1 and Comparative Examples 1 to 3. As shown in FIG. [Diagram 5] FIG. 5 is a graph showing the maximum stress value when the negative electrode model of each example was rolled from the surface facing the current collector. [Figure 6] FIG. 6 is a graph showing the liquid resistance values in the negative electrode models of each example. [Figure 7] FIG. 7 is a graph showing the correlation between the maximum stress value and the average primary particle size of the microparticles. [Figure 8] FIG. 8 is a graph showing the correlation between the liquid resistance value and the average primary particle size of the microparticles. [Figure 9] FIG. 9 is a graph showing the correlation between the maximum stress value and the packing ratio of the microparticles. [Figure 10] FIG. 10 is a graph showing the correlation between the liquid resistance value and the packing rate of the microparticles. [Figure 11] FIG. 11 is a graph showing the correlation between the maximum stress value and the uneven distribution of microparticles. [Figure 12] FIG. 12 is a graph showing the correlation between the liquid resistance value and the uneven distribution of microparticles. [Figure 13] FIG. 13 is a graph showing the correlation between maximum stress value and aspect ratio of microparticles. [Figure 14] FIG. 14 is a graph showing the correlation between the liquid resistance value and the aspect ratio of the microparticles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, an embodiment that is an example of the present disclosure will be described. These descriptions and examples are merely illustrative of the embodiment, and do not limit the scope of the invention. In the present specification, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range. In addition, in the present specification, the upper or lower limit of the numerical range may be replaced with a value shown in the examples.
[0009] Each component may contain multiple types of the corresponding substance. When referring to the amount of each component in a composition, if the composition contains multiple substances corresponding to each component, the amount refers to the total amount of those multiple substances present in the composition, unless otherwise specified. The term "process" includes not only independent processes, but also processes that cannot be clearly distinguished from other processes as long as the intended effect of the process is achieved.
[0010] In this specification, the term "peeling of the active material layer from the current collector" is a concept that encompasses a part of the active material layer being chipped off from the current collector and a part of the active material layer floating off the current collector.
[0011] ≪Electrode for secondary batteries≫ The secondary battery electrode according to the present disclosure comprises a current collector and an active material layer provided on the current collector and containing microparticles and active material particles having an aspect ratio of more than 1.0, wherein the microparticles are interposed between a plurality of the active material particles and are unevenly distributed on the current collector side, and the active material particles are oriented with their longitudinal direction approximately perpendicular to the surface direction of the current collector. According to the present disclosure, a decrease in stress caused by peeling of an active material layer from a current collector is suppressed.
[0012] A conventional secondary battery electrode and an electrode for a secondary battery according to the present disclosure will be described below with reference to the drawings. FIG. 1 is a schematic cross-sectional view in the thickness direction of a conventional electrode for a secondary battery. As shown in Fig. 1, in a conventional secondary battery electrode 100, the contact area (area R in Fig. 1) between the current collector 10 and the active material particles 30 tends to be small. This reduces the peel strength of the active material layer 20 from the current collector 10, and the active material layer 20 is likely to peel off from the current collector 10, for example, during the electrode winding step in battery production or during expansion and contraction of the active material in a cycle test. In other words, the stress tends to decrease. In addition, because the area R is small, the movement of electrons from the current collector foil to the active material particles is hindered, and resistance tends to increase.
[0013] FIG. 2 is a schematic cross-sectional view in the thickness direction of an electrode for a secondary battery in one embodiment of the present disclosure. As shown in FIG. 2, the secondary battery electrode 100 according to the present disclosure includes a current collector 10 and an active material layer 20 provided on the current collector 10 and including active material particles 30 and microparticles 50. In the active material layer 20, the active material particles 30 are oriented such that the longitudinal direction of the active material particles 30 is substantially perpendicular to the surface direction of the current collector 10. The microparticles 50 are interposed between the active material particles 30 and are unevenly distributed on the current collector 10 side. In this manner, the active material particles 30 and the microparticles 50 are in cooperative contact with the current collector 10, so that the peel strength of the active material layer 20 from the current collector 10 is high. As a result, for example, even during the electrode winding process during battery manufacturing or the expansion and contraction of the active material due to cycle testing, peeling of the active material layer 20 from the current collector 10 is suppressed, and a decrease in stress is suppressed. Furthermore, when the microparticles are conductive, the number of contact points between the current collector foil and the active material particles increases, which is thought to promote the movement of electrons and reduce resistance.
[0014] <Current collector> The secondary battery electrode according to the present disclosure has a current collector. The current collector is not particularly limited, and any current collector used in known secondary battery electrodes can be used. Examples of materials constituting the positive electrode current collector include aluminum, aluminum alloys, nickel, titanium, and stainless steel. Examples of materials constituting the negative electrode current collector include copper, copper alloys, nickel, titanium, and stainless steel.
[0015] <Resin layer> The secondary battery electrode according to the present disclosure may have a resin layer between the current collector and the active material layer. The resin layer improves the adhesion between the current collector and the active material layer. The type of resin constituting the resin layer is not particularly limited, and any known resin having excellent adhesive properties can be used.
[0016] <Active material layer> The secondary battery electrode according to the present disclosure has an active material layer provided on a current collector. The active material layer contains microparticles and active material particles having an aspect ratio of more than 1.0 (hereinafter also simply referred to as "active material particles").
[0017] [Microparticles] The microparticles are interposed between a plurality of active material particles and are unevenly distributed on the current collector side. When the fine particles are present between the active material particles and are unevenly distributed on the current collector side in the active material layer, a decrease in stress due to peeling of the active material layer from the current collector is suppressed.
[0018] The microparticles are not particularly limited as long as they can be interposed between multiple active material particles and have an average primary particle size smaller than that of the active material particles, and any microparticles used in known secondary battery electrodes can be used. Examples of the fine particles include carbon materials such as graphite and acetylene black; silicon; and the like, but are not particularly limited as long as they do not extremely reduce the electrical conductivity. Among the above, the fine particles preferably contain a carbon material, and more preferably contain graphite, from the viewpoint of more suitably interposing the fine particles between the active material particles.
[0019] The fine particles are preferably anisotropic. When the fine particles have anisotropy, aggregation of a plurality of fine particles and interposition between active material particles are easily suppressed. As a result, a decrease in stress due to peeling of the active material layer from the current collector is further suppressed.
[0020] From the viewpoint of further suppressing the reduction in stress due to peeling of the active material layer from the current collector, the microparticles preferably have an aspect ratio of 1.0 or more and 3.0 or less, more preferably 1.0 or more and 2.5 or less, and even more preferably 1.0 or more and 2.2 or less.
[0021] The aspect ratio of a microparticle refers to the ratio (long side / short side) of the length of the microparticle in the shorter direction (hereinafter also referred to as the short side) to the length of the microparticle in the longer direction (which is perpendicular to the long side) (hereinafter also referred to as the long side). The length of the microparticle in the longitudinal direction refers to the longest linear distance when connecting one end of the microparticle to the other end in the longitudinal direction. The length of the microparticle in the longitudinal direction is not particularly limited as long as it is longer than the length of the microparticle in the lateral direction. The length of the microparticle in the longitudinal direction is preferably, for example, 2.0 μm or more and 15.0 μm or less, more preferably 3.0 μm or more and 14.0 μm or less, and even more preferably 3.0 μm or more and 8.0 μm or less. The short-side length of a microparticle refers to the longest linear distance when connecting one end of the microparticle to the other end of the short-side direction. The short-side length of a microparticle is not particularly limited as long as it is shorter than the length of the microparticle in the longitudinal direction. The short-side length of a microparticle is, for example, preferably 1.0 μm or more and 7.5 μm or less, more preferably 1.0 μm or more and 5.0 μm or less, and even more preferably 1.0 μm or more and 5.0 μm or less.
[0022] The aspect ratio of the microparticles is the arithmetic average of the aspect ratios (long side / short side) between the long side and the short side of the microparticles, which is determined by observing a cross section cut along the thickness direction of the active material layer using an SEM and performing image analysis on 10 random microparticles.
[0023] The average primary particle size of the microparticles should be smaller than the average primary particle size of the active material particles. For example, from the viewpoint of more suitably disposing the microparticles between the active material particles, it is preferable that the average primary particle size be 0.30 to 0.76 times the length (μm) of the active material in the short side direction. Specifically, from the viewpoint of further suppressing the reduction in stress due to peeling of the active material layer from the current collector, the average primary particle size of the microparticles is preferably 4.58 μm or less, more preferably 1.84 μm or more and 4.58 μm or less, and even more preferably 2.00 μm or more and 4.00 μm or less. From the viewpoint of ensuring the dispersibility of the microparticles in the active material layer during production, the average primary particle size of the microparticles is preferably 1.0 μm or more, and more preferably 2.0 μm or more. The average primary particle size of the microparticles is preferably less than the length of the major axis of the active material particles, from the viewpoint of preventing the active material layer from becoming thicker in order to place small particles in the gaps between the active material particles, and from the viewpoint of maintaining an appropriate density of the active material particles in the active material layer.
[0024] The average primary particle size (D50) of the active material particles can be determined by particle size distribution measurement using a laser diffraction scattering method.
[0025] In order to further suppress a reduction in stress due to peeling of the active material layer from the current collector, it is preferable that the microparticles are unevenly distributed in a region that is not more than a depth equivalent to 0.5 times (μm) the long side of the active material particles in the thickness direction of the active material layer from the surface of the active material layer facing the current collector.
[0026] From the viewpoint of further suppressing the reduction in stress due to peeling of the active material layer from the current collector, the content of fine particles occupying a region of the active material layer from the surface of the active material layer facing the current collector to a depth equivalent to 0.5 times the long side (μm) of the active material particles in the thickness direction of the active material layer is preferably 8% by volume or more. The content of fine particles can be determined by SEM observation.
[0027] The method for distributing the fine particles unevenly in the above-mentioned region is not particularly limited, and for example, the method shown in the manufacturing method for a secondary battery electrode according to the present disclosure, which will be described later, can be applied.
[0028] The content of the microparticles in the above region is determined by performing image analysis of a cross section of the secondary battery electrode in the thickness direction using a scanning electron microscope (SEM), measuring the area of each microparticle and the area of the active material layer, and calculating the volume.
[0029] The method for adjusting the content of fine particles in the above region is not particularly limited, and for example, the method shown in the manufacturing method for a secondary battery electrode of the present disclosure, which will be described later, can be applied.
[0030] The fine particles are preferably present between a plurality of the active material particles and unevenly distributed on both the current collector side and the side facing the current collector. Fig. 3 is a cross-sectional schematic diagram in the thickness direction of a secondary battery electrode in another embodiment of the present disclosure. As shown in Fig. 3, a secondary battery electrode 100 in another embodiment according to the present disclosure has a current collector 10 and an active material layer 20 provided on the current collector 10 and including active material particles 30, microparticles 40, and microparticles 50. In the active material layer 20, the active material particles 30 are oriented such that the longitudinal direction of the active material particles 30 is substantially perpendicular to the surface direction of the current collector 10. The microparticles 50 are interposed between the multiple active material particles 30 and are unevenly distributed on the current collector 10 side. The microparticles 40 are interposed between the multiple active material particles 30 and are unevenly distributed on the side facing the current collector 10 (i.e., the side on which an electrolyte layer is provided when a secondary battery is formed). When the microparticles 40 are included that are unevenly distributed on the side opposite to the current collector 10 in addition to the microparticles 50 unevenly distributed on the side opposite to the current collector 10, for example, when pressing is performed from the surface opposite to the current collector 10 during the manufacture of a secondary battery, the microparticles 40 interposed between the active material particles 30 reduce the pressure applied to the active material particles 30. This reduces the loss of orientation of the active material particles 30. As a result, an increase in the tortuosity in the stacking direction in which electricity flows is suppressed, and a decrease in stress is further suppressed. The microparticles 40 and 50 may be different from each other in the type of material, aspect ratio, and average primary particle size, or may be the same. The preferred embodiments of the microparticles 50 are the same as those of the microparticles 40.
[0031] [Active material particles] The active material particles have an aspect ratio of greater than 1.0. The aspect ratio of the active material particles is more than 1.0, and from the viewpoint of providing better orientation and of further reducing the resistance value when the longitudinal direction of the active material particles in the active material layer is oriented approximately perpendicular to the surface direction of the current collector, it is preferably 1.5 to 4.0, and more preferably 2.0 to 3.5.
[0032] The aspect ratio of an active material particle refers to the ratio (long side / short side) of the length of the active material particle in the longitudinal direction (hereinafter also referred to as the long side) to the length of the active material particle in the lateral direction perpendicular to the long side (hereinafter also referred to as the short side). The length of the active material particle in the longitudinal direction refers to the longest linear distance when connecting one end of the active material particle to the other end of the active material particle in the longitudinal direction. The length of the active material particle in the longitudinal direction may be longer than the length of the active material particle in the lateral direction, and is preferably, for example, 8.0 μm or more and 30.0 μm or less, more preferably 10.0 μm or more and 25.0 μm or less, and even more preferably 12.0 μm or more and 20.0 μm or less. The length of the active material particle in the short side direction refers to the longest linear distance when connecting one end of the active material particle to the other end of the active material particle in the short side direction. The length of the active material particle in the short side direction may be shorter than the length of the active material particle in the longitudinal direction, and is, for example, preferably 1.0 μm or more and 10.0 μm or less, more preferably 2.0 μm or more and 9.0 μm or less, and even more preferably 3.0 μm or more and 8.0 μm or less.
[0033] The aspect ratio of the active material particles was measured by SEM of a cross section cut along the thickness direction of the active material layer. The aspect ratio is the arithmetic average value of the aspect ratio (long side / short side) of the long side to the short side of the active material particles obtained by image analysis of 10 randomly selected active material particles.
[0034] The active material particles are oriented such that the longitudinal direction of the active material particles is substantially perpendicular to the surface direction of the current collector. When the longitudinal direction of the active material particles is oriented approximately perpendicular to the surface direction of the current collector, the resistance is kept low. Here, the active material particles being oriented such that the longitudinal direction of the active material particles is substantially perpendicular to the current collector is defined as follows. A cross section cut along the thickness direction of the active material layer is observed by SEM. In the observed image, the angle (acute angle) between the longitudinal direction of 10 active material particles and the thickness direction of the active material layer is calculated. When the arithmetic mean value of the obtained angles is 5° or less, it is defined that the active material particles are oriented such that the longitudinal direction of the active material particles is approximately perpendicular to the surface direction of the current collector.
[0035] The active material particles are not particularly limited as long as they satisfy the above aspect ratio and orientation, and known active material particles used for positive and negative electrodes of secondary batteries can be used. The active material particles may be used alone or in combination of two or more types. Examples of active material particles for the positive electrode include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), lithium iron phosphate (LiFePO4), lithium nickel cobalt aluminum oxide (NCA), and lithium nickel cobalt manganese oxide (NCM).
[0036] Examples of the active material particles for the negative electrode include graphite such as natural graphite and artificial graphite, carbon materials such as hard carbon, soft carbon and activated carbon, silicon, etc. Among the above, the active material particles for the negative electrode are preferably carbon materials, and more preferably graphite (preferably flake graphite), from the viewpoint of more suitable orientation in the active material layer.
[0037] The average primary particle size of the active material particles may be larger than the average primary particle size of the microparticles, and from the viewpoint of more suitably interposing the microparticles between the active material particles and more suitably orienting the active material particles in the active material layer, it is preferably more than 4.5 μm, more preferably 5.0 μm to 25.0 μm, and even more preferably 10.0 μm to 20.0 μm. The average primary particle size (D50) of the active material particles can be determined by particle size distribution measurement using a laser diffraction scattering method.
[0038] In order to further suppress the reduction in stress due to peeling of the active material layer from the current collector, the ratio (d / R) of the longitudinal length (d) of the microparticle to the longitudinal length radius (R) of the active material particle is preferably 0.400 or more and 1.500 or less, more preferably 0.450 or more and 1.250 or less, and even more preferably 0.625 or more and 1.000 or less. The ratio (d / R) is the ratio (d / R) of the longitudinal length (d) of the microparticle to the radius (R) of the longitudinal length of the active material particle, both of which are determined by the above-mentioned measurement method. The ratio (d / R) may be controlled by adjusting the aspect ratio of the active material particles, or by adjusting the aspect ratio of the microparticles, or by adjusting both.
[0039] In order to further suppress the reduction in stress due to peeling of the active material layer from the current collector, the ratio (T / L) of the thickness T of the region of the active material layer on the current collector side where the microparticles are present to the long side L of the active material particles is preferably 0.375 or more and 0.500 or less, and more preferably 0.400 or more and 0.500 or less.
[0040] The ratio (T / L) can be calculated as follows. (1) The cross section of the active material layer in the thickness direction is observed by SEM, and the long side L (μm) of the active material particles is determined. (2) The microparticles present at the position furthest from the surface of the active material layer facing the current collector in the direction toward the current collector (i.e., the opposite direction of said surface) are identified. (3) The shortest vertical distance from the position of the microparticle to the surface facing the current collector is defined as the thickness T (μm) of the region of the active material layer where the microparticles are present. (4) Calculate the ratio (T / L). (5) The above steps (1) to (4) are carried out for any 10 microparticles identified in the above step (2), and the arithmetic mean value of the resulting ratios (T / L) is calculated.
[0041] The above ratio (T / L) may be controlled by adjusting the aspect ratio of the active material particles, or may be controlled by adjusting the thickness of the active material layer.
[0042] The thickness T (μm) of the active material layer can be appropriately designed depending on the desired performance of the secondary battery electrode, etc., but from the viewpoint of further suppressing the reduction in stress due to peeling of the active material layer from the current collector, it is preferably 20.0 μm or more and 50.0 μm or less, more preferably 25.0 μm or more and 45.0 μm or less, and even more preferably 25.0 μm or more and 40.0 μm or less.
[0043] From the viewpoint of battery performance and further suppressing the reduction in stress due to peeling of the active material layer from the current collector, the content of the active material particles is preferably 30 volume % or more and 70 volume % or less, and more preferably 40 volume % or more and 60 volume % or less, relative to the active material layer.
[0044] [Other materials] The active material layer may further contain other materials than the microparticles and active material particles that can be contained in the active material layer of the secondary battery electrode, such as binder resins, conductive assistants, thickeners, surfactants, dispersants, wetting agents, and defoamers, within the scope of the effects of the present disclosure.
[0045] The secondary battery electrode of the present disclosure may be either a positive electrode or a negative electrode. The secondary battery electrode of the present disclosure is preferably used, for example, as a negative electrode. When active material particles having an aspect ratio of more than 1.0 are used as the negative electrode active material layer and the longitudinal direction is arranged perpendicular to the current collector foil, the active material generally expands in the short direction during charging, so that the active material layer is likely to peel off due to expansion in the direction parallel to the foil (the direction in which the binding force as a battery is weak). In the secondary battery electrode according to the present disclosure, even in a secondary battery negative electrode in which peeling of the active material layer from the current collector is likely to occur, the reduction in stress due to peeling of the active material layer from the current collector is suppressed.
[0046] The secondary battery electrode of the present disclosure can be used as an electrode for various secondary batteries such as lithium ion secondary batteries, sodium ion secondary batteries, and lithium ion polymer secondary batteries.
[0047] ≪Secondary battery≫ The secondary battery according to the present disclosure is a secondary battery including the secondary battery electrode according to the present disclosure. The secondary battery according to the present disclosure is, for example, a secondary battery including the secondary battery electrode according to the present disclosure and an electrolyte layer. The electrolyte layer may be a known electrolyte layer, and may be either a solid electrolyte layer or a liquid electrolyte layer. According to the secondary battery according to the present disclosure, a decrease in stress caused by peeling of the active material layer from the current collector is suppressed even during operation of the battery. The secondary battery according to the present disclosure may be a lithium ion secondary battery, a sodium ion secondary battery, a lithium ion polymer secondary battery, or other various secondary batteries, but is preferably a lithium ion secondary battery.
[0048] <Method for manufacturing secondary battery electrode> The method for manufacturing an electrode for a secondary battery according to the present disclosure includes the steps of: applying a first slurry containing active material particles having an aspect ratio of more than 1.0, a solvent, and microparticles onto a current collector; applying a second slurry containing active material particles and a solvent but no microparticles; and orienting the longitudinal direction of the active material particles within an active material layer approximately perpendicular to the surface direction of the current collector. According to the method for producing a secondary battery electrode according to the present disclosure, the above steps provide an electrode for a secondary battery in which a reduction in stress due to peeling of the active material layer from the current collector is suppressed even during battery operation.
[0049] [First coating process] In the first coating step, a first slurry containing active material particles having an aspect ratio of more than 1.0 and a solvent is coated onto a current collector. The first slurry contains the microparticles according to the present disclosure. The active material particles may be the same as those described in the secondary battery electrode according to the present disclosure. As the solvent, a known solvent in which active material particles or fine particles can be dispersed may be used.
[0050] [Second coating process] In the second coating step, a second slurry that does not contain microparticles in the first slurry is coated. Microparticles may be included to the extent that they do not affect the characteristics. A known solvent that disperses active material particles or microparticles can be used as the solvent.
[0051] The first coating step may be a step of coating a first slurry onto the active material particles, the first slurry including active material particles in addition to microparticles and a solvent, and having a higher microparticle content than the microparticle content of the second slurry. By configuring the first slurry to also contain active material particles, it is possible to more efficiently interpose the microparticles between a plurality of active material particles and to unevenly distribute the microparticles on the side facing the current collector.
[0052] The order of the first coating step and the second coating step is not particularly limited and may be any of the following specifications 1) to 3). From the viewpoint of efficiently distributing the fine particles on the current collector side, however, 1) or 2) is preferable, and 1) is more preferable: 1) A specification in which the first coating step is carried out simultaneously (i.e., the first slurry and the second slurry are mixed and coated on the current collector); 2) A second coating process is carried out after the first coating process; 3) The first coating process is carried out after the second coating process.
[0053] In addition, when the microparticles are to be unevenly distributed on the side opposite the current collector in addition to the current collector side (i.e., for example, in the case of an electrode for a secondary battery as shown in FIG. 3), an active material layer in which the microparticles are unevenly distributed on the current collector side may be formed, and then an active material layer in which the microparticles are unevenly distributed on the side opposite the current collector may be formed by, for example, re-applying a second slurry.
[0054] [Orientation process] In the orientation step, the longitudinal direction of the active material particles is oriented substantially perpendicular to the surface direction of the current collector in the active material layer, thereby suppressing an increase in the tortuosity.
[0055] The order of the orientation step is not particularly limited as long as it is performed after the first coating step, and may be any of the following 1) to 3): 1) A specification in which the first coating step is followed by an orientation step and then a second coating step (however, in this case, the content of active material particles in the second slurry is 5% by mass or less, more preferably 0% by mass, based on the total material contained in the second slurry, i.e., it is preferable that the second slurry does not contain active material particles); 2) A specification in which the first coating process and the second coating process are carried out in this order, followed by an orientation process; 3) The first and second coating processes are carried out simultaneously, followed by the orientation process.
[0056] In addition, when the microparticles are to be unevenly distributed on the side opposite the current collector in addition to the current collector side (i.e., for example, in the case of an electrode for a secondary battery as shown in FIG. 3), after forming an active material layer in which the microparticles are unevenly distributed on the current collector side and the orientation of the active material particles is adjusted by an orientation process, the first slurry may be applied again to re-orient the active material particles, thereby forming an active material layer in which the microparticles are unevenly distributed on the side opposite the current collector.
[0057] The method for orienting the active material particles substantially perpendicular to the surface direction of the current collector is not particularly limited and can be appropriately designed depending on the active material particles to be used. For example, the method includes applying a magnetic field to the active material layer via the current collector.
[0058] [Other steps] The method for producing an electrode for a secondary battery according to the present disclosure may further include other steps in addition to the above-mentioned first coating step, second coating step, and orientation step. Examples of the other steps include the following 1) to 3): 1) a drying step of drying the active material layer after the orientation step; 2) a rolling step of rolling the active material layer dried in the drying step; 3) Cutting or trimming the secondary battery electrode to a desired size. In the method for producing a secondary battery electrode of the present disclosure, even if the rolling step 2) above is performed, the loss of material orientation in the active material layer is suppressed, and a decrease in stress is suppressed.
[0059] The method for producing an electrode for a secondary battery according to the present disclosure preferably includes a step of producing an electrode for a secondary battery according to the present disclosure.
[0060] <Secondary battery manufacturing method> The method for manufacturing a secondary battery according to the present disclosure is a method for manufacturing a secondary battery that includes a step of manufacturing a secondary battery including an electrode for a secondary battery manufactured by the method for manufacturing an electrode for a secondary battery according to the present disclosure. According to the method for producing an electrode for a secondary battery according to the present disclosure, a secondary battery can be obtained in which a decrease in stress due to peeling of the active material layer from the current collector is suppressed even during battery operation. EXAMPLES
[0061] Examples will be described below, but the present invention is not limited to these examples. In the following description, unless otherwise specified, all "parts" and "%" are based on mass.
[0062] <Example 1> (Simulation conditions) Using GeoDict software (manufactured by Math2Market), a negative electrode model for a lithium ion secondary battery was created, which had a current collector, a resin layer, and an active material layer in that order. Specifically, the current collector model was a metal plate with a thickness of 0.4 μm. A resin layer with a thickness of 0.4 μm was placed between the current collector and the active material layer as an adhesive layer that adheres the current collector and the active material layer. The active material layer model was designed so that the active material particles were oriented with their longitudinal direction approximately perpendicular to the surface direction of the current collector. The active material layer model was designed so that microparticles were interposed between multiple active material particles and were unevenly distributed on the current collector side. The thickness of the active material layer was 30 μm. The model conditions for the microparticles and active material particles are shown below.
[0063] Active material particles: flake graphite (long side 16.0 μm, short side 8.0 μm, aspect ratio (long side / short side) = 2.0) · Microparticles: Acetylene black (carbon material, average primary particle size 4.0 μm), the content was 3 volume % relative to the active material layer.
[0064] Fig. 4 is a schematic cross-sectional view in the thickness direction of the active material layer model in Example 1 and Comparative Examples 1 to 3. Fig. 4(D) shows a schematic cross-sectional view in the thickness direction of the active material layer model in Example 1. In the figure, the tip side in the direction of the arrow is the surface in contact with the current collector.
[0065] As shown in FIG. 4(D), the microparticles were unevenly distributed in a region from the surface of the active material layer facing the current collector to a depth corresponding to the long side (μm) of the active material particles in the thickness direction of the active material layer.
[0066] The content of microparticles in a region from the surface of the active material layer facing the current collector in the thickness direction of the active material layer to a depth equal to or less than 0.5 times the long side (μm) of the active material particles was set to 11.49 vol.%.
[0067] The active material layer model was designed so that the ratio (T / L) of the thickness T of the area where the microparticles are present on the current collector side to the long side L of the active material particle was 1.875 (T=30.0 μm / L=16.0 μm).
[0068] The ratio (d / R) of the length (d) in the longitudinal direction of the microparticle to the radius (R) of the length in the longitudinal direction of the active material particle was 0.36 (d=3 μm / R=8 μm).
[0069] <Comparative Example 1> Using the same software as in Example 1, a negative electrode model for a lithium ion secondary battery having a current collector, a resin layer, and an active material layer in this order was produced. In the active material layer model, a magnetic field was applied, and the active material particles were oriented such that the longitudinal direction of the active material particles was approximately perpendicular to the surface direction of the current collector. In addition, in the active material layer model, fine particles were interposed between a plurality of active material particles and were dispersed throughout the active material layer. The current collector and the resin layer were the same as those in Example 1. The model conditions for the active material particles are shown below. 4(A) shows a schematic diagram of a cross section in the thickness direction of the active material layer model of Comparative Example 1. In the figure, the tip side in the direction of the arrow is the surface in contact with the current collector.
[0070] Active material particles: flake graphite (long side 16.0 μm, short side 8.0 μm, aspect ratio (long side / short side) = 2.0) The thickness T of the active material layer is 30.0 μm.
[0071] <Comparative Example 2> Using the same software as in Example 1, a negative electrode model for a lithium ion secondary battery having a current collector, a resin layer, and an active material layer in this order was produced. In the active material layer model, the active material particles were designed so that the longitudinal direction of the active material particles was not oriented substantially perpendicular to the surface direction of the current collector. The current collector and the resin layer were designed to be the same as in Example 1. The model conditions for the active material particles are shown below. 4(B) shows a schematic cross-sectional view in the thickness direction of the active material layer model of Comparative Example 2. In the figure, the tip side in the direction of the arrow is the surface in contact with the current collector.
[0072] Active material particles: flake graphite (long side 16.0 μm, short side 8.0 μm, aspect ratio (long side / short side) = 2.0) The thickness T of the active material layer is 30.0 μm.
[0073] <Comparative Example 3> Using the same software as in Example 1, a negative electrode model for a lithium ion secondary battery having a current collector, a resin layer, and an active material layer in this order was produced. In the active material layer model, a magnetic field was applied, and the active material particles were oriented such that the longitudinal direction of the active material particles was approximately perpendicular to the surface direction of the current collector. In addition, in the active material layer model, the microparticles were dispersed throughout the active material layer. The current collector and the resin layer were the same as those in Example 1. The model conditions for the active material particles and the microparticles are shown below. 4(C) shows a schematic diagram of a cross section in the thickness direction of the active material layer model of Comparative Example 2. In the figure, the tip side in the direction of the arrow is the surface in contact with the current collector.
[0074] · Active material particles: flake graphite (long side 16.0 μm, short side 6.0 μm, aspect ratio 2.7) · Microparticles: acetylene black (carbon material, average primary particle size 3.0 μm) The content of the microparticles was 11.19% by volume with respect to the active material layer. The thickness T of the active material layer is 30.0 μm.
[0075] The content of microparticles in the region up to a depth equivalent to the long side (μm) of the active material particles in the thickness direction of the active material layer from the surface of the active material layer facing the current collector was set to 11.19% by volume.
[0076] The ratio (d / R) of the length (d) in the longitudinal direction of the microparticle to the radius (R) of the length in the longitudinal direction of the active material particle was 0.36 (d=3 μm / R=8 μm).
[0077] <Evaluation of maximum stress> For the active material layer model of each example, when the surface facing the current collector (i.e. the surface in contact with the electrolyte layer) is rolled, the maximum von Mises stress (hereinafter referred to as "maximum stress") applied between the adhesive layer and the active material layer when the microparticles unevenly distributed on the current collector side in the active material layer in contact with the resin layer are displaced by 0.4 μm was obtained by simulation. The simulation conditions were SoftGeoDict (manufactured by MATH2MARKET), calculation conditions: stress when the electrode plate is compressed by 5%, active material particles (Young's modulus 32 (MPa), Poisson's ratio 0.32, linear expansion coefficient 8e -7 (1 / K)). The results are shown in Figure 5. Note that the higher the maximum stress on the current collector side, the stronger the force required to peel the active material layer from the current collector, i.e., the stronger the peel strength.
[0078] FIG. 5 is a graph showing the maximum stress value when the negative electrode model of each example was rolled from the surface facing the current collector. As shown in FIG. 5, the negative electrode model of Example 1 has a higher maximum stress value than the negative electrode models of Comparative Examples 1 to 3, suggesting that the active material layer is less likely to peel off from the current collector.
[0079] <Evaluation of Liquid Resistance> For each active material layer model, the solution resistance of the electrolyte in the electrode was determined by simulation. The simulation conditions were GeoDict software (manufactured by MATH2MARKET), and the calculation conditions were: electrical conductivity of solid was 0 (S / m), and ionic conductivity of the electrolyte (plate pores) was 1 (S / m). The results are shown in Figure 6. Note that the higher the solution resistance of the electrolyte, the higher the resistance when used as a secondary battery.
[0080] FIG. 6 is a graph showing the liquid resistance values in the negative electrode models of each example. 6, it was found that the negative electrode model of Example 1 had a smaller liquid resistance than the negative electrode models of Comparative Examples 2 and 3. On the other hand, the negative electrode model of Comparative Example 1 had a smaller liquid resistance than the negative electrode model of Example 1, which is suggested to be due to the fact that the negative electrode model of Comparative Example 1 does not contain microparticles and has a specification in which the longitudinal direction of the active material particles in the active material layer is oriented approximately perpendicular to the surface direction of the current collector, resulting in a smaller tortuosity.
[0081] <Evaluation of the average primary particle size of fine particles> In order to investigate the correlation between the maximum stress value or the liquid resistance value and the average primary particle size of the microparticles in the negative electrode model of Example 1, simulations were performed with the average primary particle size of the microparticles set to 1.0 μm, 2.0 μm, or 4.0 μm. The simulation conditions were the same as those in the above <Evaluation of maximum stress> or <Evaluation of liquid resistance>. The results are shown in FIG. 7 and FIG. 8, respectively.
[0082] Fig. 7 is a graph showing the correlation between the maximum stress value and the average primary particle size of the microparticles. Fig. 8 is a graph showing the correlation between the liquid resistance value and the average primary particle size of the microparticles. 7 and 8, it was found that when the average primary particle size of the microparticles is 2.00 μm or more and 4.58 μm or less (more preferably 4.00 μm or less), good results are obtained in terms of both maximum stress and liquid resistance. It was also suggested that the maximum stress tends to increase as the average primary particle size of the microparticles decreases.
[0083] <Evaluation of the packing ratio of microparticles> In order to investigate the correlation between the maximum stress value or the liquid resistance value and the packing rate of the microparticles in the negative electrode model of Example 1, simulations were performed with the packing rate of the microparticles set to 8.6 volume%, 17.3 volume%, 34.5 volume%, or 43.2 volume%. The simulation conditions were the same as those in the above-mentioned <Evaluation of maximum stress> or <Evaluation of liquid resistance>. The results are shown in Figures 9 and 10, respectively. The packing rate refers to the content (volume %) of the microparticles in a region that occupies a region from the surface of the active material layer facing the current collector to a depth equivalent to 0.5 times (μm) the long side of the active material particles in the thickness direction of the active material layer.
[0084] FIG. 9 is a graph showing the correlation between the maximum stress value and the packing ratio of the microparticles. FIG. 10 is a graph showing the correlation between the liquid resistance value and the packing rate of the microparticles. As shown in FIG. 9 and FIG. 10, it was found that when the filling rate of the microparticles was 26 volume % to 34.5 volume %, better results were obtained for both the maximum stress and the liquid resistance. It was found that increasing the filling rate increases the maximum stress, in other words, the peel strength tends to increase, and that a filling rate of 8 volume percent or more ensures the peel strength. On the other hand, it was also found that increasing the filling rate tends to increase the liquid resistance.
[0085] <Evaluation of uneven distribution of microparticles> In order to investigate the correlation between the value of maximum stress or the value of liquid resistance and the uneven distribution of microparticles in the active material layer of the negative electrode model of Example 1, the uneven distribution of microparticles was changed from Example 1 as follows, and simulations were performed for each. Specifically, the content of microparticles in the entire active material layer was fixed at 3 volume % as in Example 1, while the content of microparticles unevenly distributed in the region of the active material layer from the surface on the current collector side to the thickness direction of the active material layer at a depth equal to or less than 0.5 times the long side (μm) of the active material particles (hereinafter also referred to as "uneven distribution") was changed from 1.0 in Example 1 to 0.267, 0.50, 0.67, and 0.80 with respect to the content of microparticles in the entire active material layer. The simulation conditions were the same as those of the above-mentioned <Evaluation of maximum stress> or <Evaluation of liquid resistance>. The results are shown in FIG. 11 and FIG. 12, respectively.
[0086] FIG. 11 is a graph showing the correlation between the maximum stress value and the uneven distribution of microparticles. FIG. 12 is a graph showing the correlation between the liquid resistance value and the uneven distribution of microparticles. 11 and 12, it was found that the maximum stress tends to increase as the degree of uneven distribution of microparticles increases, that is, the peel strength tends to increase. On the other hand, it was suggested that the liquid resistance does not tend to depend on the degree of uneven distribution of microparticles.
[0087] <Evaluation of anisotropy of microparticles> In order to investigate the correlation between the maximum stress value or the liquid resistance value and the anisotropy of the microparticles in the negative electrode model of Example 1, the long side of the microparticles was changed and the aspect ratio was set to 1.00, 1.25, 1.50, 2.00, 2.50, or 3.00, and a simulation was performed. The short side of the microparticles in each example had the same specifications as in Example 1. The simulation conditions were the same as those in the above <Evaluation of maximum stress> or <Evaluation of liquid resistance>. The results are shown in Figures 13 and 14, respectively.
[0088] Fig. 13 is a graph showing the correlation between the maximum stress value and the aspect ratio of the microparticles. Fig. 14 is a graph showing the correlation between the liquid resistance value and the aspect ratio of the microparticles.
[0089] As shown in Fig. 13, it was found that the maximum stress tends to be better when the aspect ratio of the microparticles is 3 or less. In addition, as shown in Fig. 14, it was found that the liquid resistance tends to decrease as the aspect ratio of the microparticles increases. [Explanation of symbols]
[0090] 100 secondary battery electrode, 10 current collector, 20 active material layer, 30 active material particles, 40 microparticles, 50 microparticles
Claims
1. A current collector; an active material layer provided on the current collector, the active material layer including microparticles and active material particles having an aspect ratio of more than 1.0; having the microparticles are interposed between a plurality of the active material particles and are unevenly distributed on the current collector side, The active material particles are oriented such that a longitudinal direction of the active material particles is substantially perpendicular to a surface direction of the current collector.
2. 2. The electrode for a secondary battery according to claim 1, wherein the microparticles are unevenly distributed in a region having a depth equivalent to 0.5 times the length (μm) of the long side of the active material particles in a thickness direction of the active material layer from a surface of the active material layer facing the current collector.
3. 2. The electrode for a secondary battery according to claim 1, wherein a content of the microparticles in a region not exceeding a depth equivalent to 0.5 times the long side (μm) of the active material particles in a thickness direction of the active material layer from the surface of the active material layer facing the current collector is 8% by volume or more.
4. 2. The electrode for a secondary battery according to claim 1, wherein a ratio (T / L) of a thickness T of a region of the active material layer on the current collector side where the microparticles are present to a long side L of the active material particles is 0.375 or more and 0.500 or less.
5. The electrode for a secondary battery according to claim 1 , wherein the active material particles are graphite.
6. The electrode for a secondary battery according to claim 1 , which is for a negative electrode.
7. The electrode for a secondary battery according to claim 1 , wherein the microparticles have anisotropy.
8. The electrode for a secondary battery according to claim 7 , wherein the microparticles have an aspect ratio of 1.0 or more and 2.5 or less.
9. 2. The electrode for a secondary battery according to claim 1, wherein a ratio (d / R) of a longitudinal length (d) of the microparticle to a radius (R) of the longitudinal length of the active material particle is 0.625 or more and 1.000 or less.
10. 2 . The electrode for a secondary battery according to claim 1 , wherein the fine particles are interposed between a plurality of the active material particles and are unevenly distributed on both the current collector side and the side facing the current collector.
11. The electrode for a secondary battery according to claim 1 , wherein the microparticles have an average primary particle size of 4.58 μm or less.
12. A secondary battery comprising the electrode for secondary batteries according to any one of claims 1 to 11.
13. A step of applying a first slurry containing active material particles and microparticles having an aspect ratio of more than 1.0 and a solvent onto a current collector; applying a second slurry containing the active material particles and a solvent but not containing the microparticles; orienting the active material particles in an active material layer such that their longitudinal directions are substantially perpendicular to a surface direction of the current collector; The method for producing an electrode for a secondary battery comprising the steps of:
14. A method for producing a secondary battery, comprising the step of producing a secondary battery comprising the electrode for a secondary battery produced by the method for producing an electrode for a secondary battery according to claim 13.
Citation Information
Patent Citations
Manufacturing method for graphite containing composition, manufacturing method for negative electrode for lithium secondary battery, and manufacturing method for lithium secondary battery
JP2003197189A
Secondary battery
JP2013004307A